1979
DOI: 10.1042/cs0560157
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy in Bone Loss of Ageing: Improvement by Treatment with 1α-hydroxycholecalciferol and Calcium

Abstract: 1. Eleven patients with the bone loss of ageing were treated with the vitamin D analogue 1 alpha-hydroxycholecalciferol and calcium for 3--6 months. 2. Muscle biopsies were taken from the vastus lateralis before and after the treatment and the activity of several enzymes was measured. Succinate dehydrogenase and total phosphorylase activities, which are a measure of the oxidative capacity, were low and increased significantly with the treatment. The lactate dehydrogenase activity, which can be taken as a measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
179
0
15

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(197 citation statements)
references
References 9 publications
3
179
0
15
Order By: Relevance
“…Changes in muscle morphology include derangement of the intermyofibrillar network, increases in intramuscular lipids, and atrophy of the fast‐twitch white (type 2) fibres,11, 44, 48, 49 which are the first to be recruited when preventing a fall. All these changes seem to be reversible,50 supporting co‐ordinated effects of vitamin D in musculoskeletal physiology 51, 52, 53, 54…”
Section: Vitamin D Physiologymentioning
confidence: 88%
“…Changes in muscle morphology include derangement of the intermyofibrillar network, increases in intramuscular lipids, and atrophy of the fast‐twitch white (type 2) fibres,11, 44, 48, 49 which are the first to be recruited when preventing a fall. All these changes seem to be reversible,50 supporting co‐ordinated effects of vitamin D in musculoskeletal physiology 51, 52, 53, 54…”
Section: Vitamin D Physiologymentioning
confidence: 88%
“…First, the VDR is expressed in human muscle tissue, (37,38) although this was questioned recently, (39) and VDR activation may promote de novo protein synthesis in muscle. (40) Mice lacking the VDR show a skeletal muscle phenotype with smaller and variable muscle fibers and persistence of immature muscle gene expression during adult life. (34,41) Second, proximal muscle weakness is a prominent feature of the clinical syndrome of vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Sorenson et al showed that fast-twitch type II muscle fibers atrophy in the absence of 1.25(OH) 2 D 3 and reappear by treatment with alfacalcidol [35]. Analogues of 1.25(OH) 2 D 3 (D-hormone) have been shown to have an effect on muscle power and neuromuscular coordination [39,43,46,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of 1.25(OH) 2 D 3 , which are significantly above the lowest defined normal value of 1.25(OH) 2 D 3 , respectively associated increases in iPTH serum levels, have been shown to have a negative impact on muscle strength and functional mobility [8,9] and have been related to myopathy [9,10,11,28,34]. Serum levels of 1.25(OH) 2 D 3 have been associated with decreased muscle strength, lower endurance [8,9,10,11,12], reduced functional mobility [13,14], and atrophy of fast-twitch muscle fibers [35]. Also, 1.25(OH) 2 D 3 is an effective treatment of the iPTH-related decrease of energy metabolism in skeletal muscle and proteolysis of muscle proteins [36,37,38].…”
Section: Discussionmentioning
confidence: 99%